A JWST/MIRI view of the interstellar medium in M83. I. Resolved molecular hydrogen properties, star formation, and feedback - Jones, Logan H.; Hernandez, Svea; Smith, Linda J.; Togi, Aditya; Diaz-Santos, Tanio; Aloisi, Alessandra; Blair, William; Hirschauer, Alec S.; Hunt, Leslie K.; James, Bethan L.; Kumari, Nimisha; Lebouteiller, Vianney; et al. (The astrophysical journal, 2025)
We present a spatially resolved (∼3 pc pixel−1) analysis of the distribution, kinematics, and excitation of warm H2 gas in the nuclear starburst region of M83. Our JWST/MIRI integral field unit spectroscopy reveals a clumpy reservoir of warm H2 (>200 K) with a mass of ∼2.3 × 105 M⊙ in the area covered by all four Medium Resolution Spectrometer (MRS) channels. We additionally use the [Ne II] 12.8 μm and [Ne III] 15.5 μm lines as tracers of the star formation rate (SFR), ionizing radiation hardness, and kinematics of the ionized interstellar medium (ISM), finding tantalizing connections to the H2 properties and stellar populations (e.g., broad and blueshifted [Ne II] emission coincident with a region with >5 Myr old stellar populations, low SFR, and low H2 surface density.) Finally, qualitative comparisons to the trove of public, high-spatial-resolution multiwavelength data available on M83 shows that our MRS spectroscopy potentially traces all stages of the process of creating massive star clusters, from the embedded protocluster phase through the dispersion of ISM from stellar feedback.